PECULIARITIES OF THE ERADICATION THERAPY FOR CHRONIC GASTRODUODENITIS ASSOCIATED WITH H. PYLORI IN CHILDREN, RESIDING IN ECOLOGICALLY UNFAVORABLE ENVIRONMENT - N.V. Zaitseva; A.I. Aminova; A.A. Akatova; E.Yu. Minchenko (Union of pediatricians of Russia, 2009)
Nowadays, H. pylori contamination spread among people became a pandemic, including children population. Persistence of the given infection may lead not only to marked inflammatory changes in the mucous coat of stomach and duodenum but also to metastatic processes. It is undoubtedly necessary to duly perform an adequate eradication therapy. The authors of the given study share their experience in treatment of children with chronic H. pylori associated gastroduodenitis.Key words: H. pylori, eradication, children.